1984
DOI: 10.1021/bi00319a005
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a human cDNA for .alpha.2-thiol proteinase inhibitor and its identity with low molecular weight kininogen

Abstract: A lambda gt11 cDNA library containing DNA inserts prepared from human liver mRNA has been screened with an antibody to human alpha 2-thiol proteinase inhibitor that was isolated from fresh plasma. Eighteen positive clones were isolated from one million phage, and each was plaque purified. The cDNA insert of one of these phage was sequenced and shown to code for alpha 2-thiol proteinase inhibitor as identified by a partial amino acid sequence of the light chain of alpha 2-thiol proteinase inhibitor. This cDNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
100
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 231 publications
(109 citation statements)
references
References 31 publications
8
100
1
Order By: Relevance
“…Cystatin-like sequences identified in the kininogens (Ohkubo et al, 1984) were found to be present as sequence duplications. Subsequently, it was proposed that there were three cystatin-like repeats in the kininogen sequence, the amino terminal repeat being Reprint requests to: K.M Dziegielewska, Department of Anatomy and Physiology, University of Tasmania, GPO Box 252-24, Hobart, Tasmania 7001, Australia.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Cystatin-like sequences identified in the kininogens (Ohkubo et al, 1984) were found to be present as sequence duplications. Subsequently, it was proposed that there were three cystatin-like repeats in the kininogen sequence, the amino terminal repeat being Reprint requests to: K.M Dziegielewska, Department of Anatomy and Physiology, University of Tasmania, GPO Box 252-24, Hobart, Tasmania 7001, Australia.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of a cystatin "superfamily" emerged in the early 1980s, precipitated by an observation that multiple cystatin-like sequences were present in the kininogens and that the stefins were related to both the cystatins and the repeats in the kininogens (Ohkubo et al, 1984). The cystatins are a family of cysteine protease inhibitors with homology to chicken cystatin (Barrett, 1981).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations